The Relationship between Education Level and Scabies Prevention Behavior of Santri in Pondok Pesantren Y Pati - Nissa Anggraeni; Nina Anggraeni Noviasari; Chamim Faizin (Jurnal Indonesia Sosial Sains, 2024)
Scabies can be prevented by implementing healthy behaviors such as scabies prevention behaviors. This can help reduce the spread of scabies transmission in boarding schools. One of the risk factors for scabies is the level of education. The incidence of scabies is mostly experienced by MTs students rather than MA students. Because MTs students tend to have poor scabies prevention behavior. In relation to the incidence of scabies in individuals, exposure experience is a crucial aspect because individuals of more mature age, namely MA students, have better potential in knowing how to prevent scabies. The purpose of this study was to determine the relationship between education level and the prevention behavior of scabies in students at Pondok Pesantren Y Pati. This study applied analytic observational method with cross sectional research design. The research sample was 56 male and 87 female students of Pondok Pesantren Y Pati who were selected through total sampling technique. The research instrument was a scabies prevention behavior questionnaire that had been tested for validity and reliability by Umi Hasanah, 2019. Data were analyzed by applying the chi square test at a significance level of 95%. There is a significant relationship between education level and scabies prevention behavior p = 0.000, with a PR value = 14.695. With the characteristics of male respondents = 56 students (39.2%), female = 87 students (60.8%), MTs = 93 students (65.0%), MA = 50 students (35%), students who experience scabies = 62 students (43.4%), students who do not experience scabies = 81 (56.6%). The level of education can affect the behavior of preventing scabies in students. There is a significant relationship between the level of education and the behavior of preventing scabies in students in boarding school Y pati.